2020
DOI: 10.1002/cncr.33362
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of the “Day 100 Talk”: An interdisciplinary communication intervention during the first six months of childhood cancer treatment

Abstract: Background Communication gaps arise early in the childhood cancer trajectory and may persist. The authors conducted a pilot study of the feasibility and acceptability of a communication intervention, the Day 100 Talk (D100). D100 involves an interprofessional family conference during initial months of treatment between oncologists, psychosocial clinicians, and parents, facilitated by a 3‐part conversation tool. Methods The authors enrolled English‐speaking parents of children with nonrelapsed, nonprogressive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 70 publications
(86 reference statements)
0
20
0
Order By: Relevance
“…A bilingual interviewer trained in medical sociology conducted parent interviews 8 . Parents described communication experiences receiving childhood cancer care and reviewed/gave feedback on Spanish language Day100 materials, including the three‐part communication tool (preparatory family worksheet, conversation guide, and family summary sheet), 3 and parent surveys. Interpreters and clinicians discussed experiences communicating with Spanish‐speaking parents and identified benefits and potential barriers to conducting Day100 with Spanish‐speaking families.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A bilingual interviewer trained in medical sociology conducted parent interviews 8 . Parents described communication experiences receiving childhood cancer care and reviewed/gave feedback on Spanish language Day100 materials, including the three‐part communication tool (preparatory family worksheet, conversation guide, and family summary sheet), 3 and parent surveys. Interpreters and clinicians discussed experiences communicating with Spanish‐speaking parents and identified benefits and potential barriers to conducting Day100 with Spanish‐speaking families.…”
Section: Methodsmentioning
confidence: 99%
“…The Day100 Talk (Day100) is an intervention to bridge communication gaps between parents and clinicians through an interprofessional family conference facilitated by communication tools during the initial months of childhood cancer care. Day100 provides families of children with cancer an opportunity to regroup with their child's care team to address unanswered questions, concerns, and future goals 3 . In a recent study, Day100 exceeded predetermined feasibility thresholds (60% parent intervention completion) and was highly acceptable to families and clinicians 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For patients who receive diagnoses with extremely poor prognosis, many families are open to PC integration at diagnosis. 16,[23][24][25][26][27] In practice, pediatric oncologists often wait for a precipitating event such as relapse or code status discussion to introduce PC. 2,12,17,28 However, many events arise during a child's cancer course that cause distress.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have shown that families are accepting of PC within the first few months following diagnosis, as symptom‐related suffering begins early during treatment. For patients who receive diagnoses with extremely poor prognosis, many families are open to PC integration at diagnosis 16,23–27 …”
Section: Introductionmentioning
confidence: 99%